2021
DOI: 10.48550/arxiv.2109.14526
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the reliability of published findings using the regression discontinuity design in political science

Drew Stommes,
P. M. Aronow,
Fredrik Sävje

Abstract: The regression discontinuity (RD) design offers identification of causal effects under weak assumptions, earning it the position as a standard method in modern political science research. But identification does not necessarily imply that the causal effects can be estimated accurately with limited data. In this paper, we highlight that estimation is particularly challenging with the RD design and investigate how these challenges manifest themselves in the empirical literature. We collect all RD-based findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Alternatively, the negative effect we identify might resemble a more durable form of preference change that is stable even years after the war was concluded. Since our data is constructed of repeated cross-sectional surveys rather than a panel survey, and since any given cross-sectional survey alone is underpowered to identify our main estimates (Stommes et al, 2021), we are not ideally set up to fully address the question of effect durability.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the negative effect we identify might resemble a more durable form of preference change that is stable even years after the war was concluded. Since our data is constructed of repeated cross-sectional surveys rather than a panel survey, and since any given cross-sectional survey alone is underpowered to identify our main estimates (Stommes et al, 2021), we are not ideally set up to fully address the question of effect durability.…”
Section: Resultsmentioning
confidence: 99%
“…Our formal RDiT models are estimated using the rdrobust (Calonico, Cattaneo, and Titiunik 2015) package in R, which allows for the estimation of nonparametric bandwidths (i.e., a bandwidth around the cutpoint that is driven by the inherent properties of the data and not selected by the researcher), bias-corrected point estimates, and robust standard errors. We thus sidestep the major problems recently associated with RDD designs (Stommes, Aronow, and Sävje 2021). We use a local polynomial of 1 to avoid over-fitting the data.…”
Section: Testing the Effects On Voter Turnoutmentioning
confidence: 99%
“…In particular, Gaussian process methods had interval coverage almost always at or near the desired level. This is important, as recent work has found that most existing methods that are used for RDD designs tend to understate uncertainty and provide anti-conservative inference (Stommes et al, 2021). This work has been further extended to spatial RDD settings where the goal is estimation of the treatment effect curve on a two-dimensional boundary (Rischard et al, 2020).…”
Section: Regression Discontinuity Designsmentioning
confidence: 99%